A outra face do reencantamento: o niilismo moderno no pensamento de Lima Vaz. - Lima, Hélio Pereira (2019)
The purpose of this paper was to discuss the question of "religious revival", termed "re-enchantment" or "return of the sacred", in order to verify if this concept is a category of analysis sufficient to understand present religious movements in their complex singularity – either as existential answers to the lack of meaning caused by the crisis of values of modernity or as witnesses of the human desire for transcendence, in their inescapable hope that human history is not exhausted in nothingness. The method used was the historical-hermeneutic, which enabled a dialogical approach between the Religion Sciences, Sociology and Philosophy in the effort to apprehend, comprehensively, such phenomenon that resists to descriptions simply explanatory, what makes this work a singularly qualitative research. In order to reach the objective, it was necessary to compose a socio-historical referential framework to apprehend the phenomenon in the broad context of the objectifications of such religious experiences, in addition to the explanatory discourses. For that, we used the contributions of Max Weber on Western rationalization and Lima Vaz's analysis of nihilism. From the process of rationalization, unique in the West, the goal was to verify that such phenomenon, born at the heart of religion, is contrary to the disenchantment of the world. From Lima Vaz's analysis, it was seen that nihilism also traced the path of disenchantment and the consequent loss of meaning. Revealing itself as an enigma, nihilism took hold on the structural axis of the modern West, since normative referents of the humanist tradition were replaced by the hypertrophied subjectivity of the ego cogito, erected as the last frontier upon which the individual establishes the truth of himself and of the world. Ethical nihilism is, thus, the ultimate expression of an enigma that defies the understanding of modernity and at the same time clarifies its own contradictions because it is a time when denying the transcendent values that nurtured hope in a reconciled humanity imposes the individual himself as a source of value – who in struggle to find the meaning of existence resorts to the shelter of religious experiences, signs of human desire for transcendence. Therefore, on the assumption of the analyzes of the constitution of modern times and the crisis of meaning caused by the abandonment of transcendent values, it is understood that "reenchantment" is an insufficient notion to explain the emergence of religious movements, because such a category of analysis cannot explain the place of religion in this reenacted world, in the face of the persuasive force of the immanent values produced by formal and operative rationality, the main driving force of progress. As an inquiry, was the formation of a new normative framework in which religion would reassume the role of symbolic force generating meaning and guiding human history? What place would occupy subjectivity, the normative principle of modern times, in this new configuration? If the concept of re-enchantment does not give satisfactory answers to these questions, then it is presumed necessary to resort to other theoretical mediations if one intends to understand the meaning of such a phenomenon at present